PENERAPAN SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA PENCURIAN ARUS LISTRIK BERDASARKAN UNDANG-UNDANG NOMOR. 30 TAHUN 2009 TENTANG KETENAGA LISTRIKAN - Kinaria Afriani; Putri Sari Nilam Cayo (Justici, 2022)
ABSTRACT Electricity theft is a crime in the electricity sector. This crime is rife in Indonesia and can cause losses for PLN as the party selling electricity. In fact, this theft can actually cause state losses, considering that PLN is a state-owned company subsidized by the state. This research is a normative juridical research, which only examines library materials or secondary data, which may include primary, secondary and tertiary legal materials. Criminal sanctions for theft of electricity are regulated in Law Number 30 of 2009 concerning Electricity, regulated in Article 49 – Article 55 In addition, the sanctions for theft of electricity are listed in Article 362 of Chapter XXII of the Criminal Code